Utility of preoperative laboratory evaluation in low-risk patients undergoing hysterectomy for benign indications. (May 2020) - Sears, Sarah; Mangel, Jeffrey; Adedayo, Pelumi; Mims, Joseph; Sundaresh, Shree; Sheyn, David
Abstract: Objective: To evaluate whether preoperative laboratory tests are predictive of surgical complications in the first 30 days after benign hysterectomy. Study Design: Data was collected from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) of patients undergoing benign hysterectomy between 2014 and 2016. Patients with significant medical comorbidities were excluded except for current smoking and hypertension. Patients were stratified into those who did and did not undergo preoperative testing. Laboratory results were stratified into normal and abnormal values. The primary outcome was the composite complication rate between groups. Student's t -test, Fisher's exact test, and Wilcoxon Rank-Sum were used for statistical analysis where appropriate. Multivariable regression analysis was used to determine which variables were independently predictive of postoperative complications. Results: A total of 24, 752 patients met all inclusion criteria. Of these, 92.5% had at least one preoperative test performed, and out of those 33.5% had an abnormal value. The most common test performed was a complete blood count, 92.5%, and the least common were coagulation studies, 16.1%. Patients who underwent testing were younger (45.9 vs 47.8 years, p < 0.001), more likely to smoke (15.3% vs 12.7%, p = 0.004) and less likely to have hypertension (18.9% vs 21.8%, p = 0.001). The most common abnormality was a low hematocrit, and the least common anomaly was an elevated international normalized ratio. The total complication rate was 9.2%, and there were no differences between groups (p = 0.07). The only lab value associated with an increased risk of complications was a hematocrit less than 34.9% (aOR 2.74, 95%CI 2.92–3.79) and WBC count >11 thousand per microliter (aOR 2.11, 95%CI 1.53–3.09). Conclusion: Non-hematologic preoperative laboratory anomalies are uncommon in healthy women undergoing benign hysterectomy by any modality and furthermore non-hematologic abnormalities are not predictive of post-operative complications. On the other hand, hematologic abnormalities are fairly common and a WBC above 11 cells per uL and hematocrit below 34.9% are predictive of postoperative complications.